Transcriptional control of quorum sensing and associated metabolic interactions in Pseudomonas syringae strain B728a - Scott, Russell A.; Lindow, Steven E. (Molecular microbiology, 2016)
Summary Pseudomonas syringae pv. syringae cell densities fluctuate regularly during host plant colonization. Previously we identified nine genes dependent on the quorum‐sensing‐associated luxR homolog ahlR during epiphytic and apoplastic stages of host colonization. Yet their contributions to host colonization remain obscure, despite ahlR regulon presence within and beyond the P. syringae pan‐genome. To elucidate AhIR regulon member functions, we characterized their regulation, interactions with each other, and contributions to the metabolome. We report Psyr_1625, encoding a functional pyruvate deydrogenase‐E1 subunit PdhQ, is required to prevent the accumulation of pyruvate in rich media. Furthermore it is exquisitely regulated by both repression of its own promoter by QrpR within a novel clade of the MarR regulator family, and co‐transcription on a 5kb transcript originating from the AhlR‐driven ahlI promoter, that reads over ahlR and qrpR. Metabolites accumulated during expression of the second AhlR‐driven operon (Psyr_1620‐1616, paoABCDE), only in a pdhQ mutant background, in addition to pyruvate, are herein associated with derepression of QrpR‐repressed pdhQ. AHL signaling, QrpR, and transcriptional read‐through events integrate to ensure AHL‐dependent expression of a novel metabolism in anticipation of environmental stress, while minimizing endogenously generated cytotoxicity. The expression of the eight genes regulated by quorum sensing in Pseudomonas syringae B728a is quite complex, exhibiting both acylhomoserine lactone (AHL)‐dependent and independent interactions. The expression of an operon conferring the production of pyruvate and apparently related small molecules is subject to both seemingly paradoxical direct positive, AHL‐dependent regulation and indirect negative regulation conferred by removal of its products by an AHL‐induced and MarR family regulator‐repressed pyruvate dehydrogenase.